Outer Membrane Vesicle‐Coated Nanoparticle Vaccine Protects against Acinetobacter baumannii Pneumonia and Sepsis. Issue 2 (22nd December 2022) - Bjanes, Elisabet; Zhou, Jiarong; Qayum, Tariq; Krishnan, Nishta; Zurich, Raymond H.; Menon, Nitasha D.; Hoffman, Alexandria; Fang, Ronnie H.; Zhang, Liangfang; Nizet, Victor
Abstract : The highly multidrug‐resistant (MDR) Gram‐negative bacterial pathogen Acinetobacter baumannii is a top global health priority where an effective vaccine can protect susceptible populations and limit resistance acquisition. Outer membrane vesicles (OMVs) shed from Gram‐negative bacteria are enriched with virulence factors and membrane lipids but heterogeneous in size and cargo. Herein, a vaccine platform combining precise and replicable nanoparticle technology with immunogenic A. baumannii OMVs (Ab‐OMVs) is reported. Gold nanoparticle cores coated with Ab‐OMVs (Ab‐NPs) induce robust IgG titers in rabbits that enhance human neutrophil opsonophagocytic killing and passively protect against lethal A. baumannii sepsis in mice. Active Ab‐NP immunization in mice protects against sepsis and pneumonia, accompanied by B cell recruitment to draining lymph nodes, activation of dendritic cell markers, improved splenic neutrophil responses, and mitigation of proinflammatory cytokine storm. Nanoparticles are an efficient and efficacious platform for OMV vaccine delivery against A. baumannii and perhaps other high‐priority MDR pathogens. Abstract : A vaccine against multidrug‐resistant Acinetobacter baumannii is a global health priority. Outer membrane vesicles (OMVs) shed from bacterial membranes are highly immunostimulatory, but heterogenous. Precision nanotechnology is used to develop a novel nanoparticle‐OMV vaccine protective against A. baumannii sepsis and pneumonia in mice, with strong B cell recruitment to draining lymph nodes, dendritic cell activation, and reduced inflammatory cytokine storm.